Lessons in chemistry - Garmus, Bonnie (New York : Doubleday, 2022)
In the early 1960s, chemist and single mother Elizabeth Zott, the reluctant star of America$1 (Bs most beloved cooking show due to her revolutionary skills in the kitchen, uses this opportunity to dare women to change the status quo.s
"Good Morning America Book Club : a GMA Book Club pick!"--Cover.
Keywords: Women scientists -- Fiction; Scientists -- Fiction; Single mothers -- Fiction; Television cooking shows -- Fiction; Sex role -- Fiction; Historical fiction; Humorous fiction